BAHASA DAN IDENTITAS BUDAYA - Santoso, Budi (Fakultas Ilmu Budaya Universitas Diponegoro, 2006)
Language is an arbitrary system of sound used by members of a social group to cooperate, communicate, and identify one self. The paper discusses the use of language to identify personal identity, social class, ethnicity, and nationality. Language can determine the identity of an individual and a group. Language is also used to identify or to show the personal identity of a person. Furthermore, language shows the social class of a person. A person who comes from the low level class has a different language style from those of the higher level class. As ethnic identity, language can be used to denote ethnicity or the membership of a person or group in a certain ethnic group. Language can also become the national identity as well. Thus, every country has its own national language